2021
DOI: 10.1111/hsc.13326
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of fear of cancer recurrence in Turkish cancer survivors who were referred for colposcopy

Abstract: 2013, 2016) and has been identified by cancer survivors as one of their major problems (Simard et al., 2013). FCR is a natural response to a cancer diagnosis and experienced on a continuum from none to severe (Cruickshank et al., 2020;Waldrop et al., 2011). The current literature suggests that FCR is associated with female gender, younger age, a higher educational background, not having a partner, having at least one child or being socially isolated, psychological distress and lower quality of life, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Only one quantitative study has been conducted to date regarding the meaning of FCR among cervical cancer survivors [ 5 ], which revealed as the three greatest fears reported by participants: what would happen to their family; pain; and disease progression (items from the Fear of Progression Questionnaire [ 10 ]). Owing to the paucity of studies regarding the meaning of FCR among cervical cancer survivors, we undertook the invitation [ 11 ] to conduct a qualitative study to gain a deeper understanding of FCR among cervical cancer survivors. A better understanding of FCR in cervical cancer survivors can help clinicians manage this problem effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Only one quantitative study has been conducted to date regarding the meaning of FCR among cervical cancer survivors [ 5 ], which revealed as the three greatest fears reported by participants: what would happen to their family; pain; and disease progression (items from the Fear of Progression Questionnaire [ 10 ]). Owing to the paucity of studies regarding the meaning of FCR among cervical cancer survivors, we undertook the invitation [ 11 ] to conduct a qualitative study to gain a deeper understanding of FCR among cervical cancer survivors. A better understanding of FCR in cervical cancer survivors can help clinicians manage this problem effectively.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many researchers have carried out relevant research on the FoP of CC patients, and previous results show that the incidence of FoP psychological dysfunction in CC patients is high in China [50]. It may be because the treatment process is painful, the treatment cycle is long, and the prognosis is poor in patients with cervical cancer, and surgery or other relevant treatments of cervical cancer may change patients' sexual function, which afects the relationship between the husband and wife, increasing the level of FoP in CC patients [51], and seriously afecting personal life and work. Fear bringing a burden to the family, fear of pain, and fear of disease progression are the 3 greatest fears in patients with cervical cancer [52].…”
Section: Discussionmentioning
confidence: 94%
“…Some quantitative and qualitative studies on samples from various cultures, cancer types, and ages have identified “worry about family” as one of the top fears underlying FCR ( Aghdam et al, 2014 ; Thewes et al, 2016 ; Hanprasertpong et al, 2017 ; Götze et al, 2019 ; Uner and Korukcu, 2021 ). Further, Uner and Korukcu (2021) have found the basis for fear of death to be fear of leaving their loved ones alone among young Turkish CSs suspected of new cancer.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%
“…Some quantitative and qualitative studies on samples from various cultures, cancer types, and ages have identified “worry about family” as one of the top fears underlying FCR ( Aghdam et al, 2014 ; Thewes et al, 2016 ; Hanprasertpong et al, 2017 ; Götze et al, 2019 ; Uner and Korukcu, 2021 ). Further, Uner and Korukcu (2021) have found the basis for fear of death to be fear of leaving their loved ones alone among young Turkish CSs suspected of new cancer. Considering this finding, it could be estimated that some CSs’ worry for their families is manifested in items or themes other than “fear of family being affected by cancer,” and family has even greater importance in their mind than the results that research shows.…”
Section: Synthesis Of Findingsmentioning
confidence: 99%